Probiotic powder ameliorates colorectal cancer by regulating Bifidobacterium animalis, Clostridium cocleatum, and immune cell composition. - Xiaojuan Yang; Qian Cao; Bin Ma; Yuhan Xia; Miao Liu; Jinhua Tian; Jian Chen; Chunxia Su; Xiangguo Duan (PLoS ONE, 2023)
Based on the relationship between the gut microbiota and colorectal cancer, we developed a new probiotic powder for treatment of colorectal cancer. Initially, we evaluated the effect of the probiotic powder on CRC using hematoxylin and eosin staining, and evaluated mouse survival rate and tumor size. We then investigated the effects of the probiotic powder on the gut microbiota, immune cells, and apoptotic proteins using 16S rDNA sequencing, flow cytometry, and western blot, respectively. The results showed that the probiotic powder improved the intestinal barrier integrity, survival rate, and reduced tumor size in CRC mice. This effect was associated with changes in the gut microbiota. Specifically, the probiotic powder increased the abundance of Bifidobacterium animalis and reduced the abundance of Clostridium cocleatum. In addition, the probiotic powder resulted in decreased numbers of CD4+ Foxp3+ Treg cells, increased numbers of IFN-γ+ CD8+ T cells and CD4+ IL-4+ Th2 cells, decreased expression of the TIGIT in CD4+ IL-4+ Th2 cells, and increased numbers of CD19+ GL-7+ B cells. Furthermore, the expression of the pro-apoptotic protein BAX was significantly increased in tumor tissues in response to the probiotic powder. In summary, the probiotic powder ameliorated CRC by regulating the gut microbiota, reducing Treg cell abundance, promoting the number of IFN-γ+ CD8+ T cells, increasing Th2 cell abundance, inhibiting the expression of TIGIT in Th2 cells, and increasing B cell abundance in the immune microenvironment of CRC, thereby increasing the expression of BAX in CRC.